Brain morphology of the threespine stickleback (Gasterosteus aculeatus) varies inconsistently with respect to habitat complexity: A test of the Clever Foraging Hypothesis. Issue 10 (4th April 2017) - Ahmed, Newaz I.; Thompson, Cole; Bolnick, Daniel I.; Stuart, Yoel E.
Abstract: The Clever Foraging Hypothesis asserts that organisms living in a more spatially complex environment will have a greater neurological capacity for cognitive processes related to spatial memory, navigation, and foraging. Because the telencephalon is often associated with spatial memory and navigation tasks, this hypothesis predicts a positive association between telencephalon size and environmental complexity. The association between habitat complexity and brain size has been supported by comparative studies across multiple species but has not been widely studied at the within‐species level. We tested for covariation between environmental complexity and neuroanatomy of threespine stickleback ( Gasterosteus aculeatus ) collected from 15 pairs of lakes and their parapatric streams on Vancouver Island. In most pairs, neuroanatomy differed between the adjoining lake and stream populations. However, the magnitude and direction of this difference were inconsistent between watersheds and did not covary strongly with measures of within‐site environmental heterogeneity. Overall, we find weak support for the Clever Foraging Hypothesis in our study. Abstract : Organisms that live in more complex habitats likely need greater neurological capacity for memory, navigation, and foraging and thus should have larger, more complex brains. Here, we used 30 populations of threespine stickleback to test for a habitat complexity/brain size relationship. Evidence for this relationship was weak, suggesting that the Clever Foraging Hypothesis may not be supported in stickleback.